Biomechanical comparison between sprint start, sled-pulling and selected squat type exercises - Okkonen, Olli (2012)
The purpose of the present study was to compare kinetics, kinematics and muscle activity between sprint start, sled-pulling and selected squat type exercises and also to examine how different exercises and variables correlate with the performance time of the block start (10 m). Nine male athletes (4 sprinters, 3 decathlonists, 1 long jumper and 1 triple jumper; mean ± SD; age = 24.9 ± 3.9 yr; height = 180.4 ± 5.9 cm; weight = 80.3 ± 7.5 kg; 100 m record = 11.35 ± 0.29 s) performed measurements and different force-time, electromyographic (EMG) and kinematic variables were compared to sprint start. Most of the comparison was done to the block phase (the phase of force production towards starting blocks) of the block start. In nearly all exercises, the activity of the gluteus maximus (GM) was significantly (p≤0.05) higher than during the block phase. The opposite was true for the activation of the biceps femoris (BF). Ground reaction forces (GRF) were highest during the 1-RM (one repetition maximum) ½-squat (SMAX). The GRFs were also significantly (p≤0.05) larger during the countermovement jumps (CMJ) with different loads and during the ½-squat with 70 % of 1-RM (S70) as compared to the block phase. The angular velocity of the knee was significantly (p≤0.05) higher during CMJs than during the block phase. The highest correlation existed between the performance time in the block start (10 m) and the takeoff velocity during CMJ (r=-0.950, p≤0.05). According to the results of the present study, it can be suggested that to overload the force production (peak and average force) of the block phase, CMJs and ½-squats could be used in training. If the aim is to activate the GM intensively, almost all of the exercises analyzed in the present study seems to be suitable. The results also indicate that CMJs could be used as supra-velocity exercise for the knee joint in the training of the block start. In addition, the correlation analyses indicate the importance of a good performance in CMJs for a good performance in the block start.